KENDALA MEDIASI PERCERAIAN PADA MAHKAMAH SYARIAH DI PANTAI BARAT SELATAN ACEH TAHUN 2016 – 2017 - Amrizal Hamsa, MA (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2020)
Mediation is an alternative solution for a case that has been developing in the society. Mediation is seen as an effective and correct in solving a divorce case within the Shari'ah Court. The challenge faced by this method is the existing of mileage parties involved, judges who are too young (inexperienced), understand only in the local language, influence from the third party, lack of mediation skills, limited room for mediation to take place, overwhelming number of divorce cases to be handled, limited time for mediation as we as a compulsion to abide to the the procedure.